Super-hydrophobic/icephobic coatings based on silica nanoparticles modified by self-assembled monolayers - Liu, Junpeng; Janjua, Zaid A.; Roe, Martin; Xu, Fang; Turnbull, Barbara; Choi, Kwing-So; Hou, Xianghui (MDPI, 2016)
A super-hydrophobic surface has been obtained from nanocomposite materials based on silica nanoparticles and self-assembled monolayers of 1H,1H,2H,2H-perfluorooctyltriethoxysilane (POTS) using spin coating and chemical vapor deposition methods. Scanning electron microscope images reveal the porous structure of the silica nanoparticles, which can trap small-scale air pockets. An average water contact angle of 163° and bouncing off of incoming water droplets suggest that a super-hydrophobic surface has been obtained based on the silica nanoparticles and POTS coating. The monitored water droplet icing test results show that icing is significantly delayed by silica-based nano-coatings compared with bare substrates and commercial icephobic products. Ice adhesion test results show that the ice adhesion strength is reduced remarkably by silica-based nano-coatings. The bouncing phenomenon of water droplets, the icing delay performance and the lower ice adhesion strength suggest that the super-hydrophobic coatings based on a combination of silica and POTS also show icephobicity. An erosion test rig based on pressurized pneumatic water impinging impact was used to evaluate the durability of the super-hydrophobic/icephobic coatings. The results show that durable coatings have been obtained, although improvement will be needed in future work aiming for applications in aerospace.